Flexible manufacture of lightweight frame structures : phase II, integration - Weinert, Klaus (Advanced materials research, 2008)
The world market's increasing demands for lightweight constructions as a means of reducing fuel consumption in transportation systems, together with shrinking materials resources, are becoming factors of major importance. These aspects are further underlined by current efforts aimed at reducing the greenhouse-gas emissions caused by production processes. In this context, considerate use of energy-intensive materials, such as aluminum, plays a major role. This increasingly important interplay between technological development, simulation of production processes and problems of integration are reflected in this interesting collection of peer-reviewed articles by leading experts in their fields. It outlines key aspects of the theoretical and experimental work involved in setting up a processing route. It will be invaluable reading material for all of those working in process design.